Development and characterization of microsatellite markers for Antennaria corymbosa (Asteraceae) and close relatives. (11th June 2019) - Thapa, Ramhari; Bayer, Randall J.; Mandel, Jennifer R.
Abstract : Premise: The genus Antennaria has a complex evolutionary history due to dioecism, excessive polyploidy, and the evolution of polyploid agamic complexes. We developed microsatellite markers from A. corymbosa to investigate genetic diversity and population genetic structure in Antennaria species. Methods and Results: Twenty‐four novel microsatellite markers (16 nuclear and eight chloroplast) were developed from A. corymbosa using an enriched genomic library. Ten polymorphic nuclear markers were used to characterize genetic variation in five populations of A. corymbosa . One to four alleles were found per locus, and the expected heterozygosity and fixation index ranged from 0.00 to 0.675 and −0.033 to 0.610, respectively. We were also able to successfully amplify these markers in five additional Antennaria species. Conclusions: These markers are promising tools to study the population genetics of sexual Antennaria species and to investigate interspecific gene flow, clonal diversity, and parentage of Antennaria polyploid agamic complexes.